2020
DOI: 10.3390/cancers12082174
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microRNAs as Innovative Biomarkers of Intestinal Diseases and Effective Players in Host-Microbiome Interactions

Abstract: Over the past decade, short non-coding microRNAs (miRNAs), including circulating and fecal miRNAs have emerged as important modulators of various cellular processes by regulating the expression of target genes. Recent studies revealed the role of miRNAs as powerful biomarkers in disease diagnosis and for the development of innovative therapeutic applications in several human conditions, including intestinal diseases. In this review, we explored the literature and summarized the role of identified dysregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 181 publications
(256 reference statements)
0
30
0
2
Order By: Relevance
“…miRNAs dysregulation observed in tissues and serum associated with disease activity was considered as a potential biomarker for clinical diagnosis ( Link et al, 2010 ; Kalla et al, 2015 ; Rupaimoole and Slack, 2017 ; Tili et al, 2017 ; Hossian et al, 2019 ; Chen et al, 2020 ), but several issues have impeded the application of circulating miRNAs in clinical diagnosis ( Wang et al, 2018 ; Saliminejad et al, 2019 ). In the host’s gastrointestinal tract, fecal miRNA can be influenced by the alteration of gut microbial composition, which provides a new perspective to identify intestinal and microbiota healthiness ( Carter et al, 2017 ; Horne et al, 2019 ; Tarallo et al, 2019 ; Sarshar et al, 2020 ).…”
Section: What Is Mirna?mentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs dysregulation observed in tissues and serum associated with disease activity was considered as a potential biomarker for clinical diagnosis ( Link et al, 2010 ; Kalla et al, 2015 ; Rupaimoole and Slack, 2017 ; Tili et al, 2017 ; Hossian et al, 2019 ; Chen et al, 2020 ), but several issues have impeded the application of circulating miRNAs in clinical diagnosis ( Wang et al, 2018 ; Saliminejad et al, 2019 ). In the host’s gastrointestinal tract, fecal miRNA can be influenced by the alteration of gut microbial composition, which provides a new perspective to identify intestinal and microbiota healthiness ( Carter et al, 2017 ; Horne et al, 2019 ; Tarallo et al, 2019 ; Sarshar et al, 2020 ).…”
Section: What Is Mirna?mentioning
confidence: 99%
“…EVs included outer membrane vesicles (OMVs) and membrane vesicles (MVs) that are, respectively, liberated by Gram-negative and Gram-positive bacteria. Various RNA species (e.g., mRNAs, miRNAs, tRNAs) are biologically active components of EVs, which may impact gene expression when being delivered to host cells ( Ahmadi Badi et al, 2017 ; Felli et al, 2017 ; Macia et al, 2019 ; Sarshar et al, 2020 ). In a fascinating study, Fábrega et al confirmed the role of OMVs in signal transduction between gut microbiota and host.…”
Section: The Implications Of Mirna For the Hostmentioning
confidence: 99%
“…Fecal miRNAs are also promising as a new way of diagnosis. The discovery of a different pattern of secreted miRNAs in disease conditions such as colorectal cancer and celiac disease, as well as the use of miRNAs to modulated gut microbiome metabolism, have paved the way for the development of new biomarkers based on these secreted molecules [ 117 ]. In the field of animal health, a total of 14 secreted miRNAs were found to be differentially expressed in bovine milk exosomes in response to a Staphylococcus aureus infection in the mammary gland [ 118 ].…”
Section: Sernas In Novel Diagnostic and Therapeutic Approachesmentioning
confidence: 99%
“…The idea of using RNA interference for therapeutic use is not new, despite the fact that patisiran, the first RNAi-based drug, was only approved in 2018 [ 122 ]. Additionally, Miravirsen, the first miRNA-targeted drug, is still under clinical validation, currently in Phase II clinical trial [ 117 ]. There is a growing hope in the use of these kinds of therapies, but the challenges associated with safety and efficiency are huge [ 122 ].…”
Section: Sernas In Novel Diagnostic and Therapeutic Approachesmentioning
confidence: 99%
“…MicroRNAs are single-stranded non-coding RNA molecules with a length varying between 18 and 23 nucleotides that operate in post-transcriptional regulation of gene expression ( 202 ). miRNAs are found in various body fluids as plasma, urine and breast milk as well as in human feces ( 103 , 143 , 203 , 204 ).…”
Section: Infant Factorsmentioning
confidence: 99%